Synthesis and Biological Evaluation of Some Quinazoline Derivatives as Antitumor and Antiviral Agents - El-Sherbeny, Magda A.; Gineinah, Magdy M.; Nasr, Magda N.; El-Shafeih, Faiza S. (Arzneimittelforschung, 2003)
A new series of 4-(4-aryl-1-piperazinyl)quinazolines 4a−f, 4-(3-substituted phenylamino)quinazoline derivatives 5a− h, 2-methoxycarbonylphenylaminoquinazoline derivatives 6a, b, 2-hydrazinocarbonylphenylaminoquinazolines 7a, b and 2-aryl-1-(substituted 4-quinazolinyl)-1,4-dihydro-5-oxo-5H-1,3,4-benzotriazepines 8a−j have been synthesized and tested for their antitumor and antiviral activities. Among them, compounds 5a−d exhibited broad spectrum antitumor activity with full panel median growth inhibition (GI50) at concentrations of 3.2, 2.0, 4.8, 4.0 µmol/l and total growth inhibittion at concentrations of 56.5, 51.0, 63.0 and 73.0 µmol/l, respectively. Compounds 7a and 7b showed moderate selectivity toward leukemia cell line. On the other hand, compounds 8a and 8b showed moderate anti HIV-1 potency with EC50 values of 40.5 and 52.8 µmol/l, respectively. The detailed synthesis, spectroscopic and biological data are reported.
Keywords: Benzotriazepinones; Quinazolines, antitumor activity, antiviral activity, synthesis